Inequality, poverty and quality of institutions: which freedom channels of globalization matter for Africa? - Simplice A. Asongu (African Governance and Development Institute (AGDI), 2013)
Are formal institutions instrumental in the effect globalization mechanisms have on the human face? If so, through which freedoms channels are poverty and inequality mitigated? With the instrumentality of formal institutions: (1) de jure financial liberalization (KAOPEN) has a positive income-redistribution impact while the de facto measure (FDI) does not; (2) political liberalization has a disequalizing effect and; (3) economic freedom has a positive (negative) effect on inequality (poverty). Hence, economic freedom does not stop the wealthy from growing wealthier, but at the same time provides for conditions that mitigate poverty. The findings broadly show that, despite the substantially documented negative incidences of some channels of globalization on poverty (and inequality), formal institutions have the capacity to device policies that will give capital openness, trade and economic liberalizations a human face. Social implications and policy options are discussed.
Keywords: F30; F41; F50; O15; O55; 330; Globalization; Inequality; Poverty; Formal institutions; Africa